Aetiopathology of rheumatoid arthritis. (April 2018) - Taylor, Peter C.; Narayan, Nehal
Abstract: Rheumatoid arthritis (RA) has a multifactorial aetiopathogenesis with both genetic and environmental factors implicated, giving rise to immune dysregulation with resultant joint inflammation and tissue damage. The emergence of biologic and small molecular targeted therapeutics has validated the role of many key molecules and cells in the pathogenesis of RA. The major cellular components, cytokines and key signalling pathways of importance in RA pathogenesis are reviewed in this article. The 'microbiome' (the population of commensals at mucosal surfaces) is also increasingly recognized to play a potential role in the pathogenesis of RA.